La construction du discours anti-djihadiste sur internet - Konowska, Agnieszka (Linguistica (Ljubljana), 2018)
The article analyses some aspects of the construction of the anti-jihadist discourse of European internet users who seem to have declared an open war against Islamist terrorists. This war is taking place on the discursive level, and it manifests itself in the form of various communication phenomena. The aim of the paper is to analyse a special kind of messages, exploiting various semiotic codes (especially visual and verbal), which attract the attention of audiences and acquire great popularity within a short time: digital memes and speech bubbles. These viral phenomena, widespread on the internet, use humour as their main tool. And since every act of humorous discourse is an act of enunciation whose strategic purpose is to turn its interlocutor into an accomplice, these messages are excellent means of discursive struggle against propaganda and jihadist acts. They are likely to produce in the audience an effect of connivance, leading the recipient to adhere to the disqualification of the target of the speech. The article describes how this disqualification enables one to attack the image of jihad and Islam in general, as well as the verbal and visual material exploited for this purpose. It also focuses on the principles and processes of the construction of the discourse in question, its humorous effects, as well as its aims and themes.
Keywords: analiza diskurza; humor; internet; islam; protidžihadističen govor